2015
DOI: 10.4067/s0718-58392015000100012
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of root growth and physiological characters in cotton after salt stress relief

Abstract: Crop growth in a saline environment depends on its tolerance to salt stress and capacity to recover after salt stress relief. To evaluate recovery mechanisms in cotton after salt stress relief, the changes of plants growth, root vigor, lipid peroxidation, antioxidant enzymes activity, organic solutes in root after salt stress relief were studied for two cotton (Gossypium hirsutum L.) cultivars (Lumianyan 37 and Sumian 22) grown under control (salt content of soil grown cotton was maintained at 0.2%), salt stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…These results were in accordance with those of Basal et al who observed a reduction in SDW and RDW with increasing salt levels in salt-tolerant and salt-sensitive cotton varieties (Basal et al, 2006). Moreover, the findings of Guo et al corroborate our results and state that under salt stress, the dry matter accumulation rate of cotton varieties decreases, but it can be resumed in the salt-tolerant varieties after recovery (Guo et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were in accordance with those of Basal et al who observed a reduction in SDW and RDW with increasing salt levels in salt-tolerant and salt-sensitive cotton varieties (Basal et al, 2006). Moreover, the findings of Guo et al corroborate our results and state that under salt stress, the dry matter accumulation rate of cotton varieties decreases, but it can be resumed in the salt-tolerant varieties after recovery (Guo et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The growth of crops under salt stress depends on their salt tolerance and resilience after the recovery ( Guo et al, 2015 ). Our analysis of the growth indices indicated an inhibitory effect of salt stress in “CS” at the R2 stage, which was significantly less in “Y1805,” especially in roots ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, 100 μM MT priming also increased the root growth rate and length in tomato ( Liu et al, 2015a ). Furthermore, MT has been shown to promote root development under abiotic stresses like salt stress ( Guo et al, 2015 ). In this study, MT treatment increased the root length, root projarea, root surface area, and root volume by 36.34, 28.52, 28.52, and 21.56%, respectively, compared with CK under DS (40–45%).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that the application of sewage sludge can increase the root vitality of rice 39 , and ryegrass 37 . The soluble sugar and amino acid contents in the bleeding sap of the plant roots are important indicators of the root penetration potential of the plant 40,41 . This study confirmed that the application of SS increased the soluble sugar and amino acid content in the bleeding sap of rice roots.…”
Section: Discussionmentioning
confidence: 99%